2014
DOI: 10.1063/1.4873836
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different components in a TPV PP/EPDM based with low hardness

Abstract: Thermoplastic vulcanizates (TPVs) are a class of polymeric material obtained by dynamic vulcanization of an elastomer in a melted thermoplastic matrix. This work intend to evaluate different variables in the production of low hardness TPVs made of polypropylene (PP) and ethylene propylene rubber (EPDM), as well the optimization of the variables looking for TPVs with improved performance. In the Study I the influence of PP crystallinity were evaluated, in the Study II the effects of different amounts of dicumyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…At constant PK-FU content the cross-link density increases with the degree of furan-functionalization of PK (and corresponding equivalent of BM). Similar behavior has been reported for rubber-based systems compounded with phenolic resins, either interpenetrating [30][31][32] or chemically bonded to the rubber matrix [33][34][35][36][37][38]. PK-BU is not able to form any DA adduct and, indeed, the reference blends with PK-BU show the lowest apparent cross-link densities, which are…”
Section: Blend Characterizationsupporting
confidence: 74%
See 1 more Smart Citation
“…At constant PK-FU content the cross-link density increases with the degree of furan-functionalization of PK (and corresponding equivalent of BM). Similar behavior has been reported for rubber-based systems compounded with phenolic resins, either interpenetrating [30][31][32] or chemically bonded to the rubber matrix [33][34][35][36][37][38]. PK-BU is not able to form any DA adduct and, indeed, the reference blends with PK-BU show the lowest apparent cross-link densities, which are…”
Section: Blend Characterizationsupporting
confidence: 74%
“…During the vulcanization stage, the phenolic resins are cured independently from the rubber, forming an interpenetrating polymer network [30][31][32]. Depending on the structure of the phenolic resins, covalent bonds can be formed between the two networks and, thus, phenolic resins can also be viewed as rigid cross-linking agents [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the values of the torque in this part are higher in the mixture containing the OMMT nanofiller due to its high strengthening effect. For the sample containing the vulcanization resin, due to the dynamic crosslinking of the elastomer in the LDPE melt, an even greater increase in the torque can be observed, which may indicate an increase in the viscosity of the mixtures due to the crosslinking reactions [15]. In this stage corresponding to the homogenization of the mixtures (Figure 1c), due to the shear forces, the temperature increases exponentially until minimum torque is reached.…”
Section: Sample Preparationmentioning
confidence: 95%
“…An increase in hardness can be observed due to the reinforcing effect of the nanofiller -the hardness value increases from 33°ShD (mixture B) to 38°ShD (mixture C) by adding 3 parts per 100 parts of rubber (phr) of OMMT nanofiller. Comparing the hardness values of mixtures A, B, C, and D, an increase in hardness can be seen with the increase in the amount of phenolic crosslinking resin, indicating that the crosslinking of the EPDM elastomer in the LDPE melt was achieved with the formation of a three-dimensional network that led to an additional reinforcement of the samples [15]. Values of elasticity or resilience (Schob) are of 16-22% and their decrease (of about 10-27%) is observed when the percentage of elastomer in the mixture decreases, as well as an improvement by dynamic crosslinking (of about 17%) of the elastomer (Figure 3).…”
Section: Mechanical Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation